The Degree of Subjective Complaints of Students Practice on Mechanical Technology Laboratories - Widana, I Ketut (Proceedings, 2018)
The working practice of the engineering students is part of the learning process that is irreducible and indispensable. The composition of lecturing between theoretical and practical one is 40% to 60%. With this condition, the students spend more time at the lab. Generally, the students perform the lab work by standing position. The research is conducted at the lab of engineering dept. on January 11, 2016 at 08.00-15.00 WITA. The design of research is observational cross sectional. The method applied is observation, interview and measuring. The subjects of research are practicing students amounting to 21 students with average ages of 19,5 ± 0,67. Body mass index on the average of 21.33 ± 2.13 kg/m2, considering  normal. Referring to the analysis of statistical test of wilcoxon signed ranks test, the difference of effect of work position is significant, namely p<0.05 towards musculoskeletal disorders (MSDs) before and after working. The quantity of the average complaint after working is 44.52 ± 9.28. The musculoskeletal complaint is felt 100% on skeletal muscles with details as follows: (a) 76% is waist ache; (b) 71% left tarsus ache; (c) 67% back pain; (d) 62% felt stiff on upper neck, lower neck and left calf ache. The result of  wilcoxon signed rank test shows that there is significant different effects of standing work position, namely p<0.05 towards fatigue generally before and after working. The degree of fatigue effects is on the average of 65% and 100% of practicin g students feel tired. Based on the questionnaire, 30 items of general fatigue are grouped into 3 (three), namely: (a) Question group 1 – 10 shows the attenuation of activity of 77%; (b) questions 11-20 show the attenuation of motivation of 86% and;  (c) questions 21-30 show the description of general physical fatigue of 53 %. The degree of working pulse is on the average of 110.00  ± 10.44 bpm (beats per minute) which can be categorized into the medium workload. By means of paired t test, the result is p<0.005. The concentration, consisted of the speed, correctness and constance also will be decrease each 15.23%, 11.20% dan 16.33%. It shows that there is a significant difference of standing work position effect towards the musculoskeletal disorders, fatigue, workload and concentration when having a rest and working of the practicing students. The efforts of working station repair, short term-rest and supplying drinking water are able to decrease musculoskeletal disorders, fatigue, workload and increase  concentration as well as increase the work productivity.